Dilemas socioambientais na comunidade São Francisco, Costa de Terra Nova no município do Careiro da Várzea - Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The São Francisco community is located in the municipality of Careiro da Várzea and has knowledge and development about the periods of seasonal phenomena. The residents of Careiro da Várzea have learned to live in harmony with these natural dynamics. Their daily practices, buildings and livelihoods are adapted to deal with the challenges and opportunities presented by the flood and ebb cycle. Thus, the aim of this study was to evaluate and identify the Socio-environmental Dilemmas in the São Francisco Community. This research was characterized by quantitative and qualitative scientific procedures and the ethnographic method, which focuses on observation strategies and the absorption of studies with groups or people. The methodological scheme of the research involved data collection, the application of forms, structured, semi-structured or open-ended interviews and photographic records, as well as a bibliographic review, with the aim of achieving the desired results. The results obtained in the study indicate that socio-environmental dilemmas refer to situations involving social and environmental issues, creating complex challenges that are intrinsically interconnected. These dilemmas result from the interdependence between human actions and ecosystems, with urban development, industrialization, intensive agriculture and resource extraction standing out. From this context, it can be seen that these dilemmas fall into the category of vulnerability, with the most significant being the lack of access to resources.
Keywords: .; .; .; CIENCIAS SOCIAIS APLICADAS; Sazonalidade; Seasonality; Adaptação; Atividades produtivas; Vulnerabilidade e Percepção Ambiental; Adaptation; Productive activities; Vulnerability and Environmental Perception